The Factors Affecting Change in the Household Economics Structure in Luang Prabang City - sayyasone, khambang; Siphanthong, Bounthavy; Sioudomphan, Soutthavone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The Research on the economic structure of households in LuangPrabang city this research aims to: 1) analyze the economic structure of households in LuangPrabang city and 2) study factors affecting changes in the economic structure of households in LuangPrabang city. This research method used a quantitative study method using closed-ended and open-ended questionnaires to collect data from a sample of 318 households. Descriptive statistics including frequency values ​​and percentages and inferential statistics including multiple regression with the ordinary least squares method were used to analyze the data using the statistical data analysis program SPSS version 27. The results found that: 1) Analyzing the household economic structure in LuangPrabang city, the household income structure of the Mano people is mainly from personal businesses. The household consumption expenditure structure of the Mano people is expenditure on food, beverages, and alcoholic beverages. The household savings structure of the Mano people found that household savings accounted for a relatively large proportion and were mostly intended for saving for daily use. In terms of the household debt structure of the Mano people, it was found that there was still a considerable amount of household debt from other sources (Share). And 2) Factors affecting changes in the household economic structure in LuangPrabang city found that household income is an important variable and has the greatest impact on changes in the household economic structure because consumption, savings, and debt are all caused by household income being too little or too much, sufficient or insufficient for consumption.